Since this question is given in standard form, meaning that it follows the form: ax^(2) + bx + c = 0, we can use the quadratic formula to solve for x:
http://www.1728.org/quadratc.htm
I think it's worthwhile to mention that a is the number that has the x^2 term associated with it. Thus, it would be 1x^(2) for this question. b is the number that has the x variable associated with it and it would be 3x, and c is a number by itself and in this case it is 2.
Now, we just plug our values into the equation like this:
x = (- (3) +- sqrt((3)^(2) - 4(1)(2)))/(2(1))
x = (-3 +-sqrt(9-8))/2
x = (-3 +- sqrt(1))/2
For these type of problems, you will obtain two solutions because of the +- part. So what you want to do is add -3 and sqrt(1) together and divide that by 2:
x = (-3+sqrt(1))/2
x = -2/2= -1
Now, we subtract sqrt(1) from -3 and divide that by 2:
x = (-3-sqrt(1))/2
x = -4/2 = -2
Therefore, the two possible solutions are:
x = -1 and x = -2